Social Value as a Mechanism for Linking Public Administrators with Society: Identifying the Meaning, Forms and Process of Social Value Creation. Issue 10 (26th July 2020) - Jain, Payal K.; Hazenberg, Richard; Seddon, Frederick; Denny, Simon
ABSTRACT: Despite public/private/third sector organisations creating and demonstrating the social value of their interventions, they face challenges in understanding and executing the process of social value creation, due to both the lack of definition and theoretically embedded explanatory models of social value. This article seeks to fill this gap by defining social value and identifying the process involved in social value creation from a Weberian standpoint of social action, class and power. Nine resource capitals were identified that contribute to the creation of social value in society: social, ethical, cultural, human/intellectual, physical, economic/financial, environmental/natural, religious, and political. The research utilises Q-methodology to develop a typology of social value and semi-structured interviews to understand the process of social value creation. The results reveal four-types of social value: action-driven, outcomes-driven, sustainability-driven and pluralism-driven, which can be derived through individual/collaborative and resource capitals-driven processes. An integrated framework for social value creation, embedded within a Weberian theoretical framework, is presented to assist policy-makers to commission social value, and public/private/third sector organisations to deliver social value.